Complete application of profiled steel sheeting dry board system as school classroom modules - Awang, Hanizam; Nordin, Norhaiza; Wan Badaruzzaman, Wan Hamidon (2008)
This paper describes the application of Profiled Steel Sheet Dry Board (PSSDB) system as innovative lightweight composite school classroom modules. The structural composite panel system consists of profiled steel sheet attached to the dry board via mechanical self drilling and self tapping screws. Compared to traditional building systems and materials, the PSSDB system eliminates the used of conventional timber formworks, columns and roof trusses in buildings. Besides, the proposed system has many advantages such as it is lightweight, making construction less labour-orientated, shorter construction time, materials optimisation, and provides better finished products. The proposed panel system falls under the Industrialised Building System (IBS) category since all the structural panel components are manufactured in a factory, transported and assembled into a structure or building with minimal additional site work. The system was successfully implemented in two school classroom modules at Sekolah Kebangsaan Telok Mas, Melaka, Malaysia.